"Dār al-Islām" revisited: territoriality in contemporary Islamic legal discourse on Muslims in the West - Albrecht, Sarah (Muslim minorities, 2018)
Front Matter -- -- Contents -- -- Introduction -- Territoriality in Islamic Legal Discourse: A Historical Outline -- Introduction to Part 1 -- Formation and Development of Territorial Concepts in the Pre-modern Period -- Debates on Territoriality in the Modern Period -- The Contemporary Islamic Legal Discourse on Territoriality -- Introduction to Part 2 -- Dār al-Islām versus Dār al-Kufr: Reinventing Traditional Binaries -- Dār al-Islām and the West: A Contractual Relationship -- Dār al-Islām Relocated: How “Islamic” is the West? -- Rethinking Territoriality beyond Dār al-Islām: Alternative Calls for Overcoming Geo-Religious Boundaries -- Why Territoriality Matters -- Introduction to Part 3 -- Territoriality, Residence, and Legal Interpretation in the West -- Territoriality, Authority, and Identity -- Conclusion.